X‐box binding protein 1 enhances adipogenic differentiation of 3T3‐L1 cells through the downregulation of Wnt10b expression. Issue 11 (19th April 2013) - Cho, Yoon Mi; Kim, Dae Hun; Kwak, Su-Nam; Jeong, Seong-Whan; Kwon, Oh-Joo
Abstract : Differentiation of preadipocytes into adipocytes is controlled by various transcription factors. Recently, the pro‐adipogenic function of XBP1, a transcription factor upregulated by endoplasmic reticulum stress, has been reported. In this study, we demonstrated that XBP1 suppresses the expression of Wnt10b, an anti‐adipogenic Wnt, during the differentiation of 3T3‐L1 preadipocytes. The expression pattern of XBP1 was reciprocal to that of Wnt10b during the early stage of adipogenesis. The intracellular protein levels of β‐catenin were negatively regulated by XBP1. Direct binding of XBP1 to the Wnt10b promoter and the subsequent decrease of the β‐catenin signalling pathway represent a novel adipogenic differentiation mechanism. Abstract : XBP1s is increased during adipogenic differentiation. Intracellular β‐catenin level is decreased by XBP1s. XBP1s directly suppresses the expression of Wnt10b. XBP1s inhibits the transcriptional activity of β‐catenin.